METODE EDUKASI KOMPLEMENTER DALAM MENINGKATKAN KEPATUHAN JADWAL IMUNISASI DI DESA SIGARA-GARA KABUPATEN DELISERDANG SUMATERA UTARA - Siregar, Gf Gustina; Sitepu, Stefani Anastasya; Hayati, Erlina; Perangin-angin, Bunga Pransiska; Napitupulu, Kelly A (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Immunization is the most effective public health intervention for preventing menular infections in babies and women. However, kepatuhan terhadap jadwal imunisasi is still a problem in many pedesaan areas, including Desa Sigara-gara, Kabupaten Deli Serdang. Factors that affect ketidakpatuhan are not limited to the availability of healthcare services; they also include aspects of knowledge, sikap, trust, and culture as well as the quality of communication between healthcare providers and the general public. This study aims to provide a comprehensive analysis of complementary education methods for improving immunization skills. The method used is literary analysis and conceptual analysis of several health education models that are relevant to the social conditions of the local community. The study's findings indicate that complementary education that is multimodal, collaborative, and community-based can increase understanding, trust, and self-awareness regarding children's immunization. Because of this, the implementation of complementary education methods is advised as a strategy to support the routine immunization program at the local level.